Association of bovine chromosome 5 markers with birth and weaning weight in Hereford cattle raised under extensive conditions - Rogberg Muñoz, Andres (2011)
Genetic markers have been used to assess the association of economically important traits with cattle under intensive feeding conditions; however, there is still the need to ascertain the usefulness of these markers under extensive production systems. Bovine chromosome 5 has been widely studied because several QTLs have been detected. Microsatellite BP1 neighboring the Myogenic factor 5 gene (Myf5), and microsatellites ETH10, IGF1 and RM029 near Insulin-like Growth Factor 1 gene (IGF1), were selected to establish their association with BLUPs (Best Linear Unbiased Predictor) for direct Birth Weight (dBW), direct Weaning Weight (dWW) and maternal Weaning Weight (mWW). Two herds were used for this objective, one commercial and the other experimental. Associations (P ≤ 0.05) between dWW and all BTA5 loci (BP1, ETH10, IGF1, and RM029) were detected. Additional associations were observed between mWW and BP1. dBW was significantly associated (P ≤ 0.05) with ETH10 genotypes and with the interaction IGF1*Herd. In particular region near BP1 could be contributing to the rare positive correlation between dWW and mWW previously found in the INTA Balcarce Station experimental herd. We confirmed marker associations with growth traits in two BTA5 regions close to previously reported QTL obtained in intensive feeding conditions; these regions affect dBW, dWW and mWW in a pasture-based system.